(3GdJhVjM hGdHjGf aj ebQC fGaY GdeOfi Hf YHO GdQMefs - (3GOQjS Hf YHO Gddgs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3GdMeO ddg GdPi efMfG cJGHg GdMcje hChLH YdjfG GdbjGe HCYHGA GdfUjMI hGdJYdje SHMGf eaQL GdcQH gPG HMhd Gddg GdJhVjM hGdHjGf ai ebQCf fGaY GdeOfi Hf YHO GdQMef LYdg SGdekG dJYdje GdUHjGf hJPcQI ddTjhN GdeGgQjf HGdbQBf s
(3BNQgG (B:s
(3heG gh EdG ef aJhMGJ Gdedc GdhgGH hEf HYO cTa GdZWGA fLhG Hi Yf Pdc aeG Ydb eKdg HYO GdNWC s
(3HgG fXGe GdJYbjHIs
(3YdjgG JUMjMGJs
(3cJHJ YfGhjfgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs